Gastrointestinal Talaromyces marneffei infection in a patient with AIDS: A case report and systematic review - Ling, Fangmei; Guo, Tao; Li, Junrong; Chen, Yidong; Xu, Mingyang; Li, Shuang; Zhu, Liangru (Frontiers in Immunology, 2022)
Talaromyces marneffei is a thermally dimorphic fungus that affects multiple organs and frequently invades immunocompromised individuals. However, only a few studies have reported the presence of intestinal infection associated with T. marneffei. Herein, we reported a case of intestinal T. marneffei infection in a man who complained of a 1-month history of intermittent fever, abdominal pain, and diarrhea. The result of the human immunodeficiency virus antibody test was positive. Periodic acid-Schiff and Gomorrah’s methylamine silver staining of the intestinal biopsy tissue revealed T. marneffei infection. Fortunately, the patient’s symptoms rapidly resolved with prompt antifungal treatment. In addition, we summarized and described the clinical characteristics, management, and outcomes of patients with intestinal T. marneffei infection. A total of 29 patients were identified, the majority of whom (65.52%) were comorbid with acquired immunodeficiency syndrome. The main clinical features included anemia, fever, abdominal pain, diarrhea, weight loss, and lymphadenopathy. The transverse and descending colon, ileocecum, and ascending colon were the most common sites of lesions. A considerable number of patients (31.03%) developed intestinal obstruction, intestinal perforation, and gastrointestinal bleeding. Of the 29 patients, six underwent surgery, 23 survived successfully with antifungal treatment, five died of T. marneffei infection, and one died of unknown causes. T. marneffei intestinal infection should be considered when immunodeficient patients in endemic areas present with non-specific symptoms, such as fever, abdominal pain, and diarrhea. Appropriate and timely endoscopy avoids delays in diagnosis. Early aggressive antifungal therapy improves the clinical outcomes of patients.